Overview of the Level of Activity Daily Living of the elderly who have chronic diseases in the Geriatric Polyclinic of the State General Hospital - Ni Wayan Suetri; Sang Ayu Ketut Candrawati; Ni Ketut Citrawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: The increase in the elderly population will of course be accompanied by an increase in the risk of suffering from chronic diseases which can accelerate functional decline and reduce the ability of the elderly to carry out important activities in daily living Activities of Daily Living (ADL Objectives: The aim of this study was to obtain a more comprehensive picture of the level of ADL independence in elderly people with chronic diseases Methods: This type of research is descriptive with a cross-sectional study design. The research sample of elderly people who had chronic diseases was 63 elderly people selected using consecutive sampling. The research instrument uses the Barthel Index. Results: The results of the study showed that of the 63 elderly people, the majority of the 39 elderly people (61.9%) who had chronic diseases experienced a mild level of dependence in carrying out daily living activities Conclusions: Chronic diseases can affect the functional abilities of elderly people in living their daily lives. The importance of educating the elderly and their families about chronic disease management, providing support to increase independence, as well as developing intervention programs that can improve the elderly's ability to carry out Activities of Daily Living (ADL).